Analytical Critical Study of Qur'an Translation - Muhammad Nur Rohman (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Understanding the Qur'an is the main factor for the sustainability of the way of life of Muslims and the religion of Islam because Muslims are not only Arabs but also from other nations or are called 'jam (foreigners) outside of Arabia, as well as more and more people. The complex and religious problems of the ummah are due to cultural acculturation and the rapid development of science which is one of the main factors. The method of translating the Qur'an with differences of opinion is still one solution to understanding it, so the translation of the Qur'an slightly reduces the problem of understanding related to the text of the verse in it, although it is still something that cannot be decipher the deep meaning associated with the purposes hidden in it.